Chronische untere Rückenschmerzen und psychische Komorbidität - Bletzer, Jutta; Gantz, Simone; Voigt, T.; Neubauer, Eva; Schiltenwolf, Marcus (Der Schmerz, 2017)
BackgroundBack pain is a common, disabling problem in Germany. Previous research has evaluated associations between low back pain (LBP), depression, and fear.ObjectivesThe results should provide ideas of how to optimize preventive measures, give guidelines for rehabilitation of patients with LBP, and to develop new therapies.Materials and methodsA systematic review of the literature including primary publications and meta-analyses using set search criteria in PubMed was performed. A meta-analysis was then done.ResultsIn all, 34 studies met the inclusion and quality criteria, whereby 14 studies were included in the meta-analysis. In the literature, significantly different depression scores were reported for people with LBP compared to a healthy control group. The pain perception in persons with LBP is associated with depression and fear. The correlation between depression and pain perception was highly significant in 5 studies (p < 0.01) and significant in 8 studies (p < 0.05). Fear and pain perception were highly significant in 4 studies (highly significant, p < 0.01) and significant in 3 studies (p < 0.05); 5 studies had no significant results. The studies were very heterogeneous.ConclusionsThe results can improve the understanding of the complexity of LBP perception and its therapy. The generalization of the results is limited. To cover the correlation of psychosocial and lifestyle factors and pain perception of LBP, further research is required. To obtain a clearer picture of pain perception in persons with LBP, standardized pain assessment would be beneficial. In addition, we recommend that future studies follow standardized procedures to allow greater comparability.